1987
DOI: 10.1016/0883-2897(87)90034-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal delivery of monoclonal antibodies: Enhanced regional delivery advantage using intravenous unlabeled anti-mouse antibody

Abstract: Radiolabeled monoclonal antibodies (MAb) delivered intraperitoneally expose cells in contact with peritoneal fluid to considerably higher levels of MAb than if the MAb dose were given intravenously. This regional delivery advantage for intact MAb is present mainly due to the relatively slow exit of MAb from the peritoneal fluid to the blood. Eventually, following i.p. injection, blood levels of MAb rise resulting in exposure of the animal to high systemic MAb levels and potential toxicity. In this series of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The faster systemic clearance of Fab can be mimicked to improve the Rd of intact IgG, as has been shown in experiments in which we have accelerated the systemic clear- ance of iodinated intact IgG by using a polyclonal antimouse antibody given systemically [21]. This approach, which presumably forms radioactive immune complexes which are then catabolized by the liver, considerably diminishes systemic exposure to radioantibody without measureable impact on i.p.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The faster systemic clearance of Fab can be mimicked to improve the Rd of intact IgG, as has been shown in experiments in which we have accelerated the systemic clear- ance of iodinated intact IgG by using a polyclonal antimouse antibody given systemically [21]. This approach, which presumably forms radioactive immune complexes which are then catabolized by the liver, considerably diminishes systemic exposure to radioantibody without measureable impact on i.p.…”
Section: Discussionmentioning
confidence: 82%
“…We have recently shown for radioiodinated intact murine IgG2ak, that increased antibody concentration compared to blood levels exists in the peritoneal cavity of rats following i.p. antibody administration [21,24]. We also showed that this i.p.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Because of its high propensity to stay confined to the peritoneal cavity until very late in the course of the disease, radiolabeled antibodies have been administered intraperitoneally in most trials. Indeed, in several preclinical and clinical studies it was demonstrated that the intraperitoneal route of administration results in higher uptake of radiolabeled antibodies in tumor as compared to the intravenous route of administration [121][122][123][124][125][126]. Other authors, however, could not confirm an advantage of intraperitoneal over intravenous administration [127].…”
Section: Ovarian Cancermentioning
confidence: 96%